Impact of Husband Support on the Success of Early Initiation of Breastfeeding: A Systematic Review - Fitriani, Azma Nur; Indrianti, Adelia; Putri, Rania Herdiani; Sandriani, Sandriani; Rosmiati, Rosmiati; Srinayanti, Yanti (Inspirasi Foundation, 2025)
Introduction: Early Initiation of Breastfeeding defined as breastfeeding within the first hour after birth, is crucial for infant health and long-term breastfeeding success. Husband support plays a vital role in facilitating this process. Objective: This study aimed to evaluate the influence of husband support on the success of Early Initiation of Breastfeeding among postpartum mothers. Methods: A systematic review was conducted by searching scientific databases including PubMed, ProQuest, Garuda, and JSTOR, covering publications from January 2014 to December 2024. The population included postpartum mothers regardless of delivery method. Husband support was assessed through questionnaires, in-depth interviews, and observation sheets. Three independent reviewers conducted article selection following the PRISMA flowchart, data extraction, and quality assessment using the CASP checklist. Extracted data comprised author details, interventions, settings, facilitators, session number and duration, methods or media used, and topics addressed. Results: Nine studies with a total of 752 participants were reviewed. The success rate of EIB with husband support ranged from 3.7% to 85.71%. Husband support involved encouragement, creating a comfortable breastfeeding environment, and jointly seeking information on EIB. Maternal knowledge and healthcare professional support were also important contributors. Conclusion: Husband support significantly influences the success of Early Initiation of Breastfeeding in postpartum mothers. Incorporating husband involvement through emotional, informational, and practical support in prenatal education programs is recommended to improve EIB outcomes.